Дочь Великого Петра: роман / Николай Гейнце - Гейнце Николай Эдуардович (Государи Руси Великой, 1994)
Экземпляры: Аб (20140807) / Инвентарный номер: 101449 / Цена: 30.00 / Авт.знак: Г 29 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1